Mechanical determinants of 100-m sprint running performance - Morin, J.-B.; Bourdin, M.; Edouard, P.; Peyrot, N.; Samozino, P.; Lacour, J.-R. (European Journal of Applied Physiology, 2012)
Sprint mechanics and field 100-m performances were tested in 13 subjects including 9 non-specialists, 3 French national-level sprinters and a world-class sprinter, to further study the mechanical factors associated with sprint performance. 6-s sprints performed on an instrumented treadmill allowed continuous recording of step kinematics, ground reaction forces (GRF), and belt velocity and computation of mechanical power output and linear force-velocity relationships. An index of the force application technique was computed as the slope of the linear relationship between the decrease in the ratio of horizontal-to-resultant GRF and the increase in velocity. Mechanical power output was positively correlated to mean 100-m speed (P < 0.01), as was the theoretical maximal velocity production capability (P < 0.011), whereas the theoretical maximal force production capability was not. The ability to apply the resultant force backward during acceleration was positively correlated to 100-m performance (r s > 0.683; P < 0.018), but the magnitude of resultant force was not (P = 0.16). Step frequency, contact and swing time were significantly correlated to acceleration and 100-m performance (positively for the former, negatively for the two latter, all P < 0.05), whereas aerial time and step length were not (all P > 0.21). Last, anthropometric data of body mass index and lower-limb-to-height ratio showed no significant correlation with 100-m performance. We concluded that the main mechanical determinants of 100-m performance were (1) a "velocity-oriented" force-velocity profile, likely explained by (2) a higher ability to apply the resultant GRF vector with a forward orientation over the acceleration, and (3) a higher step frequency resulting from a shorter contact time.